2022
DOI: 10.3390/su14148644
|View full text |Cite
|
Sign up to set email alerts
|

Research on Linear Combination Models of BDS Multi-Frequency Observations and Their Characteristics

Abstract: The linear combination of multi-frequency carrier-phase and pseudorange observations can form the combined observations with special properties. The type and number of combined frequencies will directly affect the characteristics of the combined observations. BDS-2 and BDS-3 broadcast three and five signals, respectively, and the study of their linear combination is of great significance for precision positioning. In this contribution, the linear combination form of multi-frequency carrier-phase observations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…For example, the Ω of B1I/B1C can be 25-35 times that of other dual-frequency combinations and about 45 times that of quad-and five-frequency combinations. Related studies have pointed out that, when the Ω is large, it will amplify the observation error implied by the carrier phase observations [20,34]. Therefore, combinations of Ω similar to B1I/B1C should be careful not to be used for extracting MPs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the Ω of B1I/B1C can be 25-35 times that of other dual-frequency combinations and about 45 times that of quad-and five-frequency combinations. Related studies have pointed out that, when the Ω is large, it will amplify the observation error implied by the carrier phase observations [20,34]. Therefore, combinations of Ω similar to B1I/B1C should be careful not to be used for extracting MPs.…”
Section: Methodsmentioning
confidence: 99%
“…Reasonably eliminating or reducing the effects of these errors can effectively improve the positioning accuracy [11][12][13][14]. Previous studies have shown that a reasonable combination of multiple frequency observations can reduce the impact of these errors, such as ionosphere-free combinations, ionosphere-reduced combinations, and geometric-free combinations [15][16][17][18][19][20]. With the increasing number of transmission signals, there are more favorable combinations available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to reduce the impacts of the second order of ionospheric delays, the combination coefficients can be easily obtained based on updating the A matrix with the aid of adding a column of ionospheric factors. Moreover, an example of BDS-3 five-frequency combination is presented in table 1, where the coefficients based on eliminating the second-order ionospheric delays are also listed [39]. According to the above method, an optimal IF combination of multi-frequency observations for a single GNSS system can be obtained, where all received frequencies are used to construct the observation equations.…”
Section: Methodsmentioning
confidence: 99%
“…Usually in the ionosphere-free (IF) combination case, in order to eliminate the influence of ionosphere, the combined ambiguity lose its integer nature; in contrast, the IR combination based on integer coefficients can still guarantee the integer solvability of ambiguity under the condition of almost eliminating ionosphere, which provides new opportunities for GNSS data processing. Both Feng [22] and Guo et al [23] systematically studied the selection criteria of IR combinations. Based on BDS-3 multi-frequency signals, Li et al [24,25] studied an IR combination suitable for medium-/long-baseline RTK ambiguity resolution, whose ambiguity maintains integer characteristics, and the noise level is comparable to the NL combination.…”
Section: Introductionmentioning
confidence: 99%